2020
DOI: 10.1177/1528083720941116
|View full text |Cite
|
Sign up to set email alerts
|

Development of helical auxetic yarn with negative Poisson’s ratio by combinations of different materials and wrapping angle

Abstract: Auxetic materials have negative Poisson ratio which has a multiple ranges of functional applications. The helical auxetic yarn was successfully developed through direct twist system by using core and wrap yarn or filament, which shows Auxeticity when the HAY is stretched in longitudinal direction in response it expand in transverse direction, Helical Auxetic Yarns were developed using various parameters of the core and warp filament, these parameters are wrapping angle (Twist per meter), diameter rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The comfort properties of a sock depend on its ability to transmit water (sweat) and vapor from the body to prevent accumulation of liquid on the skin. 25…”
Section: Breathabilitymentioning
confidence: 99%
“…The comfort properties of a sock depend on its ability to transmit water (sweat) and vapor from the body to prevent accumulation of liquid on the skin. 25…”
Section: Breathabilitymentioning
confidence: 99%
“…The auxetic and conventional planes of the semi-auxetic yarn [38] Figure 9. The auxetic and conventional planes of the semi-auxetic yarn [38] Since helical auxetic yarns have a high capacity for augmenting the auxetic impact of fabric, their structure may be considered as the most suitable for conducting research [21]. Most of auxetic woven fabrics has been developed by employing helical auxetic yarns and following a regular interlacement pattern, either as warp or as weft [39].…”
Section: Fundamentals Of Auxetic Yarnsmentioning
confidence: 99%
“…Thus, the structure made of the auxetic yarn is suitable for acoustic and impact absorption applications [23]. Furthermore, fabric produced from the auxetic yarn increases the mechanical properties [21]. According to Lim, the semi-auxetic yarn could be used to weave a semi-auxetic fabric.…”
Section: Fields Of Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…multifilament Polypropylene), and obtained maximum auxetic effect by varying wrap to core angle at 8°. Similarly, Ullah et al, 8 developed HAY by using a combination of high-performance fibres and conventional fibres and studied the effect of different levels of twist per metre. It was observed that the core filament of HAY increased its thickness in transverse direction under stress with considerable NPR, and its values indicated that the auxeticity had a direct relation with core filament thickness or diameter and inversely proportional to the linear density of wrap filament, in case of the wrap angle the auxeticity of HAY yarn had an inverse effect with wrap angle.…”
Section: Introductionmentioning
confidence: 99%